Beitrag zur Frage des Universitätsstudiums der Frauen : Rede zum Antritt des Rektorats der Christian-Albrechts-Universität in Kiel am 6. März 1893 - Pochhammer, L. (Leo), 1841-1920 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1893)
A lecture given by Pochhammer on the occasion of his becoming Rektor of the University of Kiel. His discussion of whether women should be admitted to the universities analyzes the areas in which women should be allowed and debates the idea of separate universities for women.